Books Reviews - Podoler, Guy; Lee, Pauline C. (Acta Orientalia Vilnensia, 2011)
Guy Podoler. Monuments, Memory, and Identity: Constructing the Colonial Past in South Korea, Welten Ostasiens. Worlds of East Asia. Mondes de l‘Extrême- Orient 18, Bern: Peter Lang AG, 2011, 272 pp., num. ill. ISBN 978-3-0343-0660-7 (hardbound), € 52.80Pauline C. Lee. Li Zhi 李贽, Confucianism and the Virtue of Desire, SUNY series in Chinese Philosophy and Culture, Albany: SUNY Press, 2012, pp. 202. ISBN 978-1-4384-3927-3 (hardcover), $75.00